2021
DOI: 10.1002/adhm.202100536
|View full text |Cite
|
Sign up to set email alerts
|

Deeply Infiltrating iRGD‐Graphene Oxide for the Intensive Treatment of Metastatic Tumors through PTT‐Mediated Chemosensitization and Strengthened Integrin Targeting‐Based Antimigration

Abstract: A limited infiltration and the subsequent low effective drug concentration result in poor chemotherapeutic outcomes against tumors, and even further promote tumor resistance and metastatic. Herein, iRGD‐modified graphene oxide (GO) nanosheets (IPHG) are developed for the intensive treatment of metastatic tumors using focus‐specific penetrated delivery together with photothermal therapy‐mediated chemosensitization and photothermal therapy‐strengthened integrin targeting‐based antimigration. In vitro and in vivo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 65 publications
0
13
0
Order By: Relevance
“…It has been reported that COS lactate (COL) has great potential for tumor imaging due to its highly efficient intracellular and site-specific delivery [79,80]. Photothermal therapy (PTT) has great potential in tumor therapy because of its low toxicity to normal tissues and high tumor ablation efficiency [81][82][83]. Sungsu Lee et al [84] reported a study on the tumor targeting property of COL and the advantages of PTT, combining COL with nearinfrared (NIR) fluorescent group ZW800-1 to form a COL-ZW800-1 (Figure 9a) conjugate for targeted cancer imaging and PTT in cancer treatment.…”
Section: Antitumor Activitymentioning
confidence: 99%
“…It has been reported that COS lactate (COL) has great potential for tumor imaging due to its highly efficient intracellular and site-specific delivery [79,80]. Photothermal therapy (PTT) has great potential in tumor therapy because of its low toxicity to normal tissues and high tumor ablation efficiency [81][82][83]. Sungsu Lee et al [84] reported a study on the tumor targeting property of COL and the advantages of PTT, combining COL with nearinfrared (NIR) fluorescent group ZW800-1 to form a COL-ZW800-1 (Figure 9a) conjugate for targeted cancer imaging and PTT in cancer treatment.…”
Section: Antitumor Activitymentioning
confidence: 99%
“…Recently, combination therapy that integrate chemotherapy with other therapeutic modalities have exhibited competitive advantages in overcoming chemoresistance [17][18][19]. Photodynamic therapy (PDT), a noninvasive treatment modality that uses photosensitizers and light to generate cytotoxic molecular species such as ROS to induce cell death, has received widespread attention in drug-resistant cancer treatment.…”
Section: Introductionmentioning
confidence: 99%
“…More importantly, GO has excellent photothermal conversion performance and has become a favourable candidate for photothermal-chemotherapy synergistic treatment. 24,25…”
Section: Introductionmentioning
confidence: 99%
“…More importantly, GO has excellent photothermal conversion performance and has become a favourable candidate for photothermal-chemotherapy synergistic treatment. 24,25 Graphene organic framework (GOF) is a new type of GO-based porous framework material formed by interconnecting multilayer GO sheets and organic ligands. Its structure and performance can be designed by controlling the type, length and concentration of organic ligands.…”
Section: Introductionmentioning
confidence: 99%